REVITALISASI KECERDASAN MAJEMUK MELALUI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BAGI GENERASI Z - Bahiroh, Jihan Nur; Suradji, Muchamad; Sun’iyah, Siti Lathifatus (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
The aim of writing this article is to provide ideas that are able to understand and apply them in learning Islamic Religious Education for generation Z with a multiple intelligence approach by Howard Gardner. There are nine multiple intelligences, namely linguistic intelligence, musical intelligence, logical-mathematical intelligence, spatial intelligence, bodily intelligence, social intelligence, personal intelligence, natural intelligence, and existential intelligence. The method used in the study is a descriptive qualitative research method involving primary data in the form of questionnaires for Generation Z (2011-2012) and interviews with Islamic Religious Education teachers at SMPN 1 Deket. The results show that natural, spatial, interpersonal, and intrapersonal intelligence are the dominant types of intelligence in Generation Z (2011-2012) and it can be concluded that the revitalization of multiple intelligences in Islamic Religious Education is not only relevant to the needs of 21st century learning, but also becomes a strategic approach in forming character and morals in the younger generation holistically.